Perlindungan Hukum Atas Hak Kekayaan Intelektual (HKI) Perhotelan di Kabupaten Lombok Barat - Fahmi, Muhammad Saiful (Lembaga Yasin AlSys, 2023)
The existence of the Mandalika National Tourism Development Strategic Area (NTDSA) is expected for West Lombok to be able to get a direct impact from the development of the tourism sector, long before NTDSA Mandalika opened, the tourism industry in West Lombok Regency itself already existed. Intellectual Property Rights (IPR) in simple terms is a right that arises for the results of thoughts that produce a product that is beneficial to humans. The form of IPR application to products in hospitality is basically divided into 2 (two), namely: First is Copyright and Rights related to Copyright. The second is Industrial Property Right. The method used in this research is normative-empirical, namely looking at the law not only as a set of normative rules or what is contained in the text of the Act but also seeing how the law can run in the midst of society While the approach used is the approach of the Act, conceptual approach, and socio-legal approach. Regulations on the protection of IPR of hotel industry have been regulated in general in Law Number 10 of 2009 concerning Tourism, Law Number 28 of 2014 concerning Copyright, Law Number 30 of 2000 concerning Trade Secrets, Law Number 31 of 2000 concerning Industrial Design, and Law Number 20 of 2016 concerning Trademarks and Geographical Indications. Legal protection of IPR for hotel industry in West Lombok Regency has so far been implemented, although there are several obstacles, hotel and restaurant industry are still less familiar with intellectual property protection for their business fields which are considered less useful so that they still have to be given consistent socialization and assistance by related parties.